2020
DOI: 10.1084/jem.2018163501152020c
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Human IgA bind a diverse array of commensal bacteria

Abstract: JEM regrets that in the original version of this paper, the x-and y-axes labels in Fig. 1 E were missing as a result of a conversion error. In addition, "colon" and "ileum" labels have been added to Fig. S1 D, and its legend has been edited for clarity. The corrected figures and legends appear below. All versions of this article have been corrected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Our follow-up studies on fish sIgT demonstrated that control of microbiota homeostasis by sIgs is a primordial function of specialized mucosal sIgs already found in early vertebrates such as teleosts ( 10 ). However, the current dogma that sIg-dependent microbiota homeostasis is mediated by sIgA or sIgT in vertebrates, has recently been challenged by several studies showing that significant proportions of human and fish microbiota are coated by sIgM in the gut and other mucosal surfaces ( 5, 18, 19 ). Because sIgM does not coat the microbiota of mice under either specific-pathogen-free (SPF) or non-SPF conditions ( 5, 7 ), laboratory mouse models to study the potential role of sIgM in host-microbiome interactions are not suitable to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…Our follow-up studies on fish sIgT demonstrated that control of microbiota homeostasis by sIgs is a primordial function of specialized mucosal sIgs already found in early vertebrates such as teleosts ( 10 ). However, the current dogma that sIg-dependent microbiota homeostasis is mediated by sIgA or sIgT in vertebrates, has recently been challenged by several studies showing that significant proportions of human and fish microbiota are coated by sIgM in the gut and other mucosal surfaces ( 5, 18, 19 ). Because sIgM does not coat the microbiota of mice under either specific-pathogen-free (SPF) or non-SPF conditions ( 5, 7 ), laboratory mouse models to study the potential role of sIgM in host-microbiome interactions are not suitable to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…IgG were isolated from serum samples diluted in 1X-PBS as previously described (29). Briefly, serum samples were loaded onto Protein G/Agarose column (Invivogen) after column equilibration.…”
Section: Purification Of Igg From Serummentioning
confidence: 99%
“…tailoring of immune responses to the situation at hand. In addition to that, the known different antigen-specificities of IgA1 and IgA2 ( 37 39 ) will further contribute to pathogen-specific immunity.…”
Section: Discussionmentioning
confidence: 99%